Evaluation of the Comparative Activity of Alcohol-Based Hand Sanitizers and Toilet Soaps against some Bacterial Isolates (Global Journal of Science Frontier Research, 2015)
This study is aimed at comparing the activity of alcohol based hand sanitizers (Dettol ® and Lovillea ® ) and toilet soaps (Lux ® and Premier ® ) against bacterial isolates. The activity of Dettol ® and Lovillea ® was compared with the activity of Lux ® and Premier ® toilet soaps against the bacterial isolates (Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus specie and Shigella specie) obtained from the palms of some individuals in Abraka, Delta state. Susceptibility of the bacterial isolates was evaluated using the agar well diffusion method by measuring the zones of inhibition observed after 24hours of incubation. Their minimum inhibitory concentrations (MIC) were also determined using the agar dilution technique. Dettol ® hand sanitizer had the highest zones of inhibition (5mm, 5mm and 3mm) against Staph aureus, Staph epidermis and Shigella specie respectively.
Keywords: sanitizers; toilet soaps; hand washing; bacterial